JURIDICAL ANALYSIS ON DISPUTE RESOLUTION IN CASES OF UNLAWFUL ACTS - Karmenita, Karmenita; Kafi Habib, Rakha; Maulida, Irma (Fakultas Hukum Universitas Swadaya Gunung Jati, 2024)
The primary purpose of the law is to realize justice; Aristotle said that justice is to give everyone what is his right. Legal facts show difficulties in resolving disputes, such as settlements that are not under the law and things considered unfair. For example, the plaintiffs felt the settlement was unfair in settling disputes concerning unlawful acts between farmers and PT PG Rajawali II. This study aims to 1) analyze the dispute resolution in the case of unlawful acts and the efforts made to resolve disputes in the case, and 2) the impact on the plaintiffs who dispute in the case using the normative juridical method with the type of qualitative research. The settlement of disputes in the case of unlawful acts is analyzed using the theory of justice; the dispute settlement efforts are not by the law and are considered unfair by the plaintiffs because what they are entitled to is not fulfilled. The plaintiffs did not receive compensation due to the defendants' destruction of land. They did not receive replacement land due to land included in the extension of the HGU, which resulted in the loss of land that the plaintiffs could use for economic activities.